Quantitative evaluation of microimpurity content in lead tungstate initial raw material and scintillation single crystals - Gudzenko, L.V.; Pantaler, R.P.; Shtitelman, Z.V.; Nazarenko, B.P.; Kosmyna, M.B.; Blank, A.B. (Functional Materials, 2005)
The results of impurity composition determination in lead tungstate raw material and in the scintillation single crystals at various stages of the technological process are presented. Iron content in the samples was determined by extraction photometry after the double-stage sample breakdown. AI, Bi, Сг, Сu, Mg, Mn, Mо, Ni, Si, Sn, and Ti were determined by atomic emission spectroscopy under arc excitation. The revealed differences in the concentration levels of the above-listed impurities in colored and colorless crystals have been demonstrated to be insufficient for make any substantial effect on the crystal light absorption. These differences have been supposed to be caused by formation of intrinsic impurities in the course of the raw material solid-phase synthesis. Наведено результати визначення домiшкового вмiсту у сировинi та монокристалах вольфрамату свинцю на рiзних стадiях технологiчного процесу. Вмiст залiза визначали екстракцiйно-фотометричним методом з двостадiйним розкриттям зразкiв. Вмiст AI, Bi, Сг, Сu, Mg, Mn, Mо, Ni, Si, Sn, Ti визначали методом атомно-емiсiйної спектрометрiї з дуговим джерелом збудження. Показано, що рiзницi, що встановлено, на рiвнi вмiсту перелiчених домiшок у забарвлених та незабарвлених кристалах недостатньо для суттевого впливу на їх свiтопоглинання. Висловлено припущення, що вказанi вiдмiнностi обумовленi появою власних домiшок у процесi твердофазного синтезу сировини. Представлены результаты определения примесного состава сырья и монокристаллов вольфрамата свинца на разных стадиях технологического процесса. Содержание железа определяли экстракционно-фотометрическим методом с двухстадийным вскрытием образцов. Содержание AI, Bi, Сг, Сu, Mg, Mn, Mо, Ni, Si, Sn, Ti определяли методом атомно-эмиссионной спектрометрии с дуговым источником возбуждения. Показано, что установленные различия в уровне содержаний перечисленных примесей в окрашенных и неокрашенных кристаллах недостаточны для существенного влияния на их светопоглощение. Высказано предположение, что указанные различия обусловлены появлением собственных примесей в процессе твердофазного синтеза сырья.